Fresno County Bar Association Bernie Witkin Luncheon at the Fresno Hilton Hotel 2nd Floor Ballroom - Watkins, Howard::::::::: (1989)
President G. Dana French, Judge Jim Paige, Bernie Witkin, Vice-President bb and Judge Lawrence O'Neill